PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INSTRINSIK CERITA LEGENDA SISWA KELAS V SDN 034 SUKAJ - Otang Kurniaman; Eddy Noviana; Misliati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
This research was based on the results of students’ ability to analyze the elements of legend stories among fifth-grade students at SDN 034 Sukajadi Pekanbaru in the second semester of the 2010/2011 academic year. Of the 30 students, only 40% achieved classical completeness, whereas the required standard was 80% of students meeting the minimum mastery criterion set by the school, which was 65.00. The research problem was formulated as whether the application of the cooperative learning model of the Numbered Heads Together (NHT) type could improve students’ ability to analyze the elements of legend stories. The purpose of this research was to improve students’ ability to analyze legend story elements through the application of the cooperative learning model of the Numbered Heads Together (NHT) type. This study employed classroom action research using the cooperative learning model of the Numbered Heads Together (NHT) type with 30 fifth-grade students at SDN 034 Sukajadi Pekanbaru. The action was conducted in May 2011. The initial results showed that the average score of students’ ability to analyze legend story elements was 60, with only 40% or 12 students achieving scores above the minimum mastery criterion. After the implementation of the Numbered Heads Together (NHT) model in the first daily test (UH I) of Cycle I, the average score increased to 68.33, with 60% or 18 students achieving mastery. In the second daily test (UH II) of Cycle II, the average score further increased to 78, with 89.91% or 27 students achieving mastery. Therefore, the research hypothesis stating that the application of the cooperative learning model of the Numbered Heads Together (NHT) type can improve the ability to analyze the elements of legend stories among fifth-grade students at SDN 034 Sukajadi Pekanbaru was accepted